Physical and mechanical characterization of sand replaced stone dust concrete. (27th August 2021) - Humayun, Muhammad; Ahad, Muhammad Zeeshan; Rehman Ghori, Ubaid ur; Naveed, Amir; Ahmad, Fawad; Arif, Muhammad; Afridi, Shaista; Sadiq, Muhammad; Jan, Saeed Ullah; Asif, Muhammad
Abstract: In this research work, physical, chemical, morphological, and mechanical behavior as partial replacement of fine aggregate in concrete. Stone dust was acquired from three different sources i.e. Nowshera, Dara, and Besai, while concrete was kept at a ratio of 1:2:4 and water to cement ratio at 0.5 as per ASTM standards for considerable workability. The compressive strength, ultrasonic pulse velocity (UPV), its correlation, density, durability test, x-ray fluorescence (XRF) analysis, and Scanning electron microscopy was carried out. Compressive strength at curing ages of 7, 14, and 28 days with 20%, 30%, and 40% replacement of sand was incorporated in concrete. The results indicated a slight increase in compressive strength at 20% replacement level for the Besai Concrete (BC), Nowshera Concrete (NC), and Dara Concrete (DC). For durability analysis; Rapid Chloride Permeability Test (RCPT) carried out on hardened stone dust-based concrete shows that with the addition of stone dust the voids between fine and coarse aggregates are filled up, less charge will pass, and ultimately durability is increased as per ASTM C 1202. The chemical composition of the stone dust samples, through XRF analysis, indicated that Silica dioxide (SiO2) compounds present in (NC), (DC), and (BC) were 13.34%, 12.339% & 11.593% respectively. The maximum compressive strength development in NC was possibly due to the presence of SiO2 compound in excess quantity in Nowshera stone dust as compared to other samples tested. Hence it can be recommended that locally available stone dust in Peshawar and its surrounding are suitable for a maximum of 40% replacement level.